Experimental studies of the joint process "hydrotransport – oil agglomeration of coal" - Biletskyi, V. S.; Oliinyk, Tetiana; Pysmennyi, Serhii; Skliar, Liudmyla; Fedorenko, Serhii; Chukharev, Serhii (Dnipro University of Technology, 2024)
Purpose. Development of highly effective dewatering methods along with preservation of technological properties of hydro-transported coal is one of the key tasks for improving modern pipeline hydrotransportation systems. Accordingly, the purpose of this study is to develop the models of “pressure loss in the pipeline – hydrotransport velocity” i = f (V) for the “water-coal-fuel oil” mixtures of different compositions, which reflect regularities of the combined process of “hydro-transport – oil agglomeration of coal”. Methods. Physical modelling of the combined process of “hydrotransport – oil agglomeration of coal” was conducted under the test-field conditions involving specialized hydrotransport installations, i.e. a coal oil granulation stand and a hydrau lic study stand. Relying on the experimental data, the trend curves were constructed, for each of which corresponding polyno mial functions were determined. Findings. In terms of test field, experimental dependencies of head losses in the pipeline i = f (V) for the water-coal-oil ag glomeration slurry were obtained based on the processing of the resulting family of statistical models for a hydrotransportation process of the indicated slurry. Originality. For the first time, polynomial regularities have been obtained that demonstrate the dependence of head losses in the pipeline i = f (V) on the composition and structure of solid and liquid phases of the water-coal-oil-agglomeration slurry. Practical implications. The research results can be used while developing the combined technology “hydrotransport – oil agglomeration of coal” and for designing corresponding industrial or main coal pipelines.

Мета. Розробка високоефективних засобів зневоднення і збереження технологічних властивостей гідротранспортованого вугілля є одним з основних завдань із вдосконалення сучасних магістральних гідротранспортних систем. Відповідно, метою даної роботи є одержання моделей “втрата напору по трубопроводу – швидкість гідравлічного транспортування” i = f (V) для водо-вугільно-мазутної суміші різного складу, які відображають закономірності протікання суміщеного процесу “гідротранспорт – масляна агло мерація вугілля”. Методика. Фізичне моделювання суміщеного процесу “гідротранспорт – масляна агломерація вугілля” проведено в полігонних умовах на спеціальних установках гідравлічного транспорту, а саме, стенді масляної грануляції вугілля та стенді гідравлічних досліджень. На основі експериментальних даних будувалися криві лінії тренду, для кожної з яких визначені відповідні поліноміальні функції. Результати. В умовах випробувального полігону одержані експериментальні залежності втрат напору по трубопроводу i = f (V) для водо-вугільно-масляно-агломераційної гідросуміші, на основі обробки одержано сімейство статистичних моделей процесу гідротранспорту вказаної гідросуміші. Наукова новизна. Вперше одержані поліноміальні закономірності, які демонструють залежність втрат напору по трубопроводу i = f (V) від складу та структури твердої і рідкої фаз водо-вугільно-масляно-агломераційної гідросуміші. Практична значимість. Результати виконаних досліджень можуть бути використані при розробці суміщеної технології “гідротранспорт – масляна агломерація вугілля” та проєктуванні відповідного промислового чи магістрального вуглепроводу.
Експериментальні дослідження суміщеного процесу "гідротранспорт – масляна агломерація вугілля"
Keywords: hydrotransport; coal; oil agglomeration; modelling; test hydrotransportation system; гідротранспорт; вугілля; масляна агломерація; моделювання; полігонна гідротранспортна установка